The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4961468
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of electronic and magnetic properties in Ni-doped WS2 monolayer

Abstract: The magnetic properties of Ni-doped WS2 monolayer are investigated using first-principles method. The results indicate that both one-Ni-doped and the nearest two-Ni-doped systems are magnetic. The p-d hybridization between the Ni atom and its neighboring S atoms results in the ferromagnetic interaction of the Ni-doped WS2 monolayer. The antiferromagnetic coupling is observed with increasing Ni-Ni distance which can be explained by two-impurity Haldane-Anderson model using quantum Monte Carlo method. Our studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The observed ferromagnetic coupling in Mo 1Àx Ni x S 2 can be explained in terms of the Zener's p-d hybridization mechanism for FM in dilute magnetic semiconductors. 47 At low Ni substitution levels, the neighboring S atoms are spin-polarized, and the strong p-d hybridization between the Ni atom with its neighbouring S atoms results in a strong FM coupling between them. At high Ni concentrations, a decrease in the grain size is also noticed, which also represents a decrease in layer number in the case of MoS 2 , thus contributing to the variation in magnetization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed ferromagnetic coupling in Mo 1Àx Ni x S 2 can be explained in terms of the Zener's p-d hybridization mechanism for FM in dilute magnetic semiconductors. 47 At low Ni substitution levels, the neighboring S atoms are spin-polarized, and the strong p-d hybridization between the Ni atom with its neighbouring S atoms results in a strong FM coupling between them. At high Ni concentrations, a decrease in the grain size is also noticed, which also represents a decrease in layer number in the case of MoS 2 , thus contributing to the variation in magnetization.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is clear that the manifestation of surface effects plays a signicant role in the magnetization of MoS 2 nanoakes. 47 The performance of the as-synthesized Mo 1Àx Ni x S 2 samples was further thoroughly investigated in the electrocatalytic hydrogen evolution reaction (HER). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Monolayer semiconducting transition metal dichalcogenides (TMDCs) of group IV transition metals, such as MoS 2 , WS 2 , and WSe 2 , exhibit direct band gaps in the visible range and a weak dielectric screening, with the latter significantly Calculations for TMDC monolayers, such as MoS 2 and WS 2 , suggest that doping with manganese, nickel, niobium, tantalum or vanadium can induce ferromagnetic order with Curie temperatures up to 170 K. [8,15,16] Among different host materials, monolayer WSe 2 is deemed especially suitable due to its good ambipolar gate tunability and larger spin-orbit splitting compared to the Mo-based TMDCs, which can be beneficial for stabilizing the magnetic order. [13,[17][18][19][20][21] Furthermore, (doped) WSe 2 bulk crystals can be grown at low defect densities, enabling proof-of-concept devices, but also high quality wafer-scale monolayers can be grown by metal organic chemical vapor deposition (CVD), ensuring scalability and applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it is possible to synthesize TM-on 2D materials using pulsed laser deposition [16] and defect-assisted doping by electron beam irradiation [17,18,19]. Both experiments and modeling works have showed that the adsorption of TM atom on 2D materials can induce magnetism [20,21,22,23,24,25,26] and depending on the nature of the TM atom, different magnetic behaviors were found. MoS 2 monolayer exhibits a magnetic behavior upon the adsorption of Cr and Co while no magnetic behaviour has been recorded in the case of Ni-adsorbed MoS 2 [27].…”
Section: Introductionmentioning
confidence: 99%